Burial and death in colonial North America : exploring interment practices and landscapes in 17th-century British settlements - Lacy, Robyn S. (Emerald Publishing Limited, 2020)
While late 17th- and 18thcentury burial grounds of colonial North America are frequently the subject of research, widescale studies of 17thcentury burial landscapes are often the less documented aspect of these sites. This book aims to fill some of that gap by exploring the relationships and organization of early British colonial burial grounds within the context of their own settlements and the wider northeast coast. Early settlers immigrated to North America for many reasons, and there, away from the Church of England, they could freely explore their relationship with their faith, community and death, represented today through the organization of their burial landscapes and burial practices. By studying the relationship between burial grounds and their associated settlements, we gain a more holistic understanding of how settlers related to, interpreted, and ultimately handled the reality of human mortality. This book examines the organization of 40 burial grounds founded by British settlers on the northeast coast of North America in the 17th century, with the intention of identifying trends in burial ground organization during this period of early colonization. The results can be applied to archaeological or historical research on colonial settlements that have not yet located their earliest burial ground. The book expands the current knowledge base of settler relationships with mortality through the physical placement of burials and interaction with burial landscapes within their new settlements.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Funeral rites and ceremonies -- United States -- History -- Colonial period, ca. 1600-1775.; United States -- History -- Colonial period, ca. 1600-1775.; Social Science, Death & Dying; Social & cultural anthropology, ethnography